Frequency Index for Learning Space in Higher Education Institutions - Nurakmal, Abdullah@ Goh Tuo Ho; Norngainy, Mohd Tawil; Che-Ani, A. I,; Azalillah Ramdani, Musa; Mazlan, Mohd Tahir (Elsevier Science, Ltd., 2012)
The aim of this study is to measure the learning space usage rate based on the teaching and learning schedule (timetable) provided by the institutions. The Frequency Index of learning space is developed by analyzing the timetable data and the list of learning spaces available at the institution. The Frequency Index is classified according to the level of usage and the interval percentage according to learning space usage frequency. This classification of Frequency Index is expressed in terms of linguistic value and the color-coded key. From this index, the institution can identify whether the existing learning space is best used or vice versa, which in turn can be a reasonable basis for the institution in need of new learning space.